Little Association between Intracranial Arterial Stenosis and Lacunar Stroke - Wardlaw, Joanna M. (S. Karger AG, 2010)
Atheromatous middle cerebral artery (MCA) stenosis could cause lacunar stroke by occluding lenticulostriate artery origins, but atheroma is common, and previous studies lacked suitable controls. We aimed to determine if intracranial atheroma was more common in lacunar than in cortical ischaemic stroke. We recruited patients with lacunar stroke and controls with mild cortical stroke, confirmed the stroke subtype with magnetic resonance imaging and used transcranial Doppler ultrasound imaging to record flow velocity and focal stenoses in the basal intracranial arteries 1 month after stroke. We compared ipsi- and contralateral MCA mean flow velocities between stroke subtypes and tested for associations using linear mixed models. Amongst 67 lacunar and 67 mild cortical strokes, mean age 64 and 67 years, respectively, we found no difference in MCA mean flow velocity between cortical and lacunar patients. Increasing age and white matter lesion scores were independently associated with lower MCA flow velocities (0.2 cms(−1) fall in velocity per year increase in age, p = 0.045; 3.75 cms(−1) fall in flow velocity per point increase in white matter lesion score, p = 0.004). We found no intracranial arterial stenoses. MCA atheromatous stenosis is unlikely to be a common cause of lacunar stroke in white populations. Falling velocities with increasing white matter lesion scores may reflect progressive brain tissue loss leaving less tissue to supply.